2008
DOI: 10.1016/j.ygyno.2007.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Improved anti-tumor therapy based upon infectivity-enhanced adenoviral delivery of RNA interference in ovarian carcinoma cell lines

Abstract: Background-Hec1 (Highly-Expressed-in-Cancer) has recently been shown to play an important role in the proper segregation of chromosomes during mitosis. Recently, an Adenovirus delivery system carrying RNA interference (RNAi) of Hec1 has been reported in a cervical adenocarcinoma model. Adenoviral delivery systems, however, have the main limitation of poor viral infectivity due to lack of the native receptor, Coxsackie-Adenovirus Receptor (CAR), on the surface of tumor cells. We hypothesize that the viral infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Dysregulation of Ndc80-NUF2 has been employed in the development of a series of human cancers, including lung cancer, colorectal cancer, gastric cancer, prostate cancer, urinary bladder cancer, renal carcinoma and ovarian cancer, rather than other normal tissues except testis [ 13 18 ]. It has been found that depletion of NUF2 by specific siRNAs (small interfering RNAs) resulted in inhibition of cell proliferation and induction of apoptosis in non-small-cell carcinoma and ovarian cancer [ 17 , 18 ]. Likewise, in colorectal and gastric cancers, after the siRNA-mediated knockdown against NUF2, cell growths were significantly suppressed, and subG1 fractions of cell cycle were significantly increased [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of Ndc80-NUF2 has been employed in the development of a series of human cancers, including lung cancer, colorectal cancer, gastric cancer, prostate cancer, urinary bladder cancer, renal carcinoma and ovarian cancer, rather than other normal tissues except testis [ 13 18 ]. It has been found that depletion of NUF2 by specific siRNAs (small interfering RNAs) resulted in inhibition of cell proliferation and induction of apoptosis in non-small-cell carcinoma and ovarian cancer [ 17 , 18 ]. Likewise, in colorectal and gastric cancers, after the siRNA-mediated knockdown against NUF2, cell growths were significantly suppressed, and subG1 fractions of cell cycle were significantly increased [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that knockdown of NUF2 suppressed pancreatic cancer proliferation in vitro and in vivo [ 18 ]. Except for the testis, dysregulation of NUF2 has been reported in the development of several human cancers, including lung cancer, colorectal cancer, prostate cancer, as compared to normal tissue [ 31 , 32 ]. Depletion of NUF2 resulted in the inhibition of cell proliferation in non-small-cell carcinoma and ovarian cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Systemic delivery systems such as retrovirus or adenovirus can target tumor cells well, but are limited to research use in animal models due to human safety issues. 19,20 Certain bacteria have great potential as siRNA delivery vectors and have already been employed in animals and humans. 2123 S. Typhimurium is an intracellular bacterial pathogen that mainly invades mucosa-associated lymphoid tissue through M cells in the intestinal mucosa and is phagocytized by macrophages and dendritic cells, in which the bacteria can proliferate.…”
Section: Discussionmentioning
confidence: 99%